2021
DOI: 10.1016/j.scitotenv.2021.146201
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of SARS-CoV-2 RNA signal in a home with COVID-19 positive occupants

Abstract: Although many COVID-19 patients isolate and recover at home, the dispersal of SARS-CoV-2 onto surfaces and dust within the home environment remains poorly understood. To investigate the distribution and persistence of SARS-CoV-2 in a home with COVID-19 positive occupants, samples were collected from a household with two confirmed COVID-19 cases (one adult and one child). Home surface swab and dust samples were collected two months after symptom onset (and one month after symptom resolution) in the household. T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
43
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 72 publications
3
43
0
1
Order By: Relevance
“…The intermittent and repeated positives could have been a result of the resuspension of dust particles containing SARS-CoV-2 genetic material. SARS-CoV-2 RNA has been detected in floor and HVAC dust up to two months after patient symptom onset (Maestre et al, 2021), which could explain our results in the absence of clinical confirmation due to the low testing participation.…”
Section: Floor and Hepa Filter Swab Sampling For The Detection Of Sars-cov-2mentioning
confidence: 74%
See 2 more Smart Citations
“…The intermittent and repeated positives could have been a result of the resuspension of dust particles containing SARS-CoV-2 genetic material. SARS-CoV-2 RNA has been detected in floor and HVAC dust up to two months after patient symptom onset (Maestre et al, 2021), which could explain our results in the absence of clinical confirmation due to the low testing participation.…”
Section: Floor and Hepa Filter Swab Sampling For The Detection Of Sars-cov-2mentioning
confidence: 74%
“…These preliminary results provided further evidence for the stability of SARS-CoV-2 RNA in the environment at least six days after deposition and validated the potential use of portable HEPA filters for environmental monitoring of COVID-19. Environmental monitoring for the presence of SARS-CoV-2 RNA through air sampling has been demonstrated in clinical and transportation settings using diverse air samplers (Barbieri et al, 2021;Moreno et al, 2021), and by swabbing or vacuuming HVAC systems (Maestre et al, 2021;Moreno et al, 2021). However, acquiring and deploying air samplers is challenging due to high costs and noise levels of these instruments.…”
Section: Validation Of Environmental Detection Of Sars-cov-2 Rna After Known Exposuresmentioning
confidence: 99%
See 1 more Smart Citation
“…Communal confined spaces such as public toilets in shopping centers, schools, restaurants, airports, theaters, and hospitals may be significant areas for SARS-CoV-2 transmission (Dancer, Li, et al, 2021). Surface contamination with SARS-CoV-2 in toilets and bathrooms has been reported (Ding, Qian, et al, 2021;Maestre, Jarma, et al, 2021); however, transmission risks from fomite exposure could be reduced significantly through the simple yet effective interventions of hand washing, hand sanitizing, and surface disinfection (Dancer et al, 2021;World Health Organization [WHO], 2020a; Pitol & Julian, 2021). Airborne transmission, on the other hand, is deemed the main route of COVID-19 spread (Centers for Disease Control and Prevention, 2021) and could be aggravated by the use of busy, confined public toilet spaces, especially if appropriate steps are not taken to mitigate the risk of virus transmission (Dancer, Li, et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…A modeling study of the spread ability by fomite transmission in aircraft showed that most of the high-touch surfaces in the cabin were contaminated within 2 or 3 h [18]. Many studies have found environments contaminated with SAR-CoV-2 in both health-care settings [19], [20], [21], [22], [23] and non-health-care settings [24], [25], [26], [27], [28], [29]. The evidence showed that SARS-CoV-2 could persist on surfaces for several hours or days [30].…”
Section: Introductionmentioning
confidence: 99%